SOME ASPECTS OF THE OPPORTUNITIES OF JUDO PLAYERS IN BULGARIA - A. Yaneva; Iv. Prokopov (Trakia Journal of Sciences)
The article presents a study of some aspects of the capabilities of current and former judo athletes. An anonymous online survey presents the opinions of 172 judokas of all ages about the techniques they practice during training and in competitions. The purpose of the study is to find out what the favorite techniques of the judokas under study are and whether they use them during a competition. The results of the study lead to conclusions about the issues related to the methodology of training and shortcomings in the training of judokas.